2020
DOI: 10.1038/s41467-020-20066-7
|View full text |Cite
|
Sign up to set email alerts
|

Strain-activated light-induced halide segregation in mixed-halide perovskite solids

Abstract: Light-induced halide segregation limits the bandgap tunability of mixed-halide perovskites for tandem photovoltaics. Here we report that light-induced halide segregation is strain-activated in MAPb(I1−xBrx)3 with Br concentration below approximately 50%, while it is intrinsic for Br concentration over approximately 50%. Free-standing single crystals of CH3NH3Pb(I0.65Br0.35)3 (35%Br) do not show halide segregation until uniaxial pressure is applied. Besides, 35%Br single crystals grown on lattice-mismatched sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 51 publications
(94 reference statements)
5
108
0
Order By: Relevance
“…It has a similar diffusion coefficient and a slightly reduced activation energy, especially for the mixing ratios x < 0.2. This reduction in activation energy could be associated with the strain in the crystal from the different bond lengths between bromide and iodide, 35 in which case the activation energy should be lowest close to the phase transition. A reduced activation energy might naively lead to an increase diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…It has a similar diffusion coefficient and a slightly reduced activation energy, especially for the mixing ratios x < 0.2. This reduction in activation energy could be associated with the strain in the crystal from the different bond lengths between bromide and iodide, 35 in which case the activation energy should be lowest close to the phase transition. A reduced activation energy might naively lead to an increase diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced symmetry of the tetragonal crystal structure leads to the increased activation energy of halide migration, accounting for the increased stability . The recent report also demonstrated that crystallization growth on lattice-mismatched substrates showed inhomogeneous segregation due to heterogeneous strain distribution …”
Section: Introductionmentioning
confidence: 99%
“…Film crystallinity and morphology when varying A and X site composition are critical in achieving photostability, since photoinduced phase segregation necessarily requires the migration or diffusion of the halide anions. , It is well accepted that ionic migration is mediated and accelerated along grain boundaries. Suppression of photoinduced halide phase segregation has been identified by A-cation alloying, B-cation alloying, and improving crystallinity. , However, few studies provide the detailed differentiation between ion migration and phase segregation under illumination. Especially, the time-dependent changes of the hybrid perovskite optical and electrical response to corresponding changes of device-level performance metrics are often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of three-dimensional (3D) perovskite films, when used as the photoactive absorber layer in PSCs, is mainly attributed to high defect densities as well as ion migration at grain boundaries and interfaces, which is exacerbated at higher operational temperatures ( 5 9 ). Several approaches have been reported to passivate these defects ( 7 , 10 13 ).…”
mentioning
confidence: 99%